2015
DOI: 10.1248/bpb.b15-00245
|View full text |Cite
|
Sign up to set email alerts
|

Peptidyl–Prolyl <i>cis</i>/<i>trans</i> Isomerase NIMA-Interacting 1 as a Therapeutic Target in Hepatocellular Carcinoma

Abstract: Phosphorylation of proteins on serine or threonine residues preceding proline is a pivotal signaling mechanism regulating cell proliferation. The recent identification and characterization of the enzyme peptidyl-prolyl cis/trans isomerase never in mitosis A (NIMA)-interacting 1 (PIN1) has led to the discovery of a new mechanism regulating phosphorylation in cell signaling. PIN1 specifically binds phosphorylated serine or threonine residues immediately preceding proline (pSer/Thr-Pro) and then regulates protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…PPIase family proteins are isomerases that shuffle disulfide bonds and allow proinsulin molecules to potentially reach their native conformation. Peptidyl-prolyl cis-trans isomerase b (PPIB) is a member of the cyclophilin-type PPIase family and contributes to protein folding ( 14 16 ). If proinsulin is not properly folded within the ER, ER stress-induced cell apoptosis occurs.…”
Section: Introductionmentioning
confidence: 99%
“…PPIase family proteins are isomerases that shuffle disulfide bonds and allow proinsulin molecules to potentially reach their native conformation. Peptidyl-prolyl cis-trans isomerase b (PPIB) is a member of the cyclophilin-type PPIase family and contributes to protein folding ( 14 16 ). If proinsulin is not properly folded within the ER, ER stress-induced cell apoptosis occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The PPIase family consists of broadly expressed enzymes that could accelerate the cis-trans proline peptide bonds isomerization. 32 PPIB, a member of the PPIase family, has been found to contribute to protein folding, 8 and its recessive mutations may result in multi-different phenotypes ranging from lethality in the perinatal period to severe deformation in osteogenesis imperfecta. 33 However, its relation with miRNAs was scarcely discussed.…”
Section: Discussionmentioning
confidence: 99%
“…PPIB (cyclophilin B, CypB), a member of the PPIase family, has been found to contribute to protein folding. 8 In cancer biology, as Choi et al pointed out, PPIB is related to malignant progression and regulation of genes. 9 As for HCC, Kim et al revealed that hypoxia-induced PPIB can stimulate HCC cell survival via a positive feedback loop with hypoxia-inducible factor-1α (HIF-1α).…”
Section: Introductionmentioning
confidence: 99%
“…Pin1 binds to the JNK-mediated Ser57 phosphorylation of the HIV-1 integrase, stabilizing its structure and further promoting integration . In addition to HIV, Pin1 is also involved in other viral infections, including hepatitis B virus (HBV), , hepatitis C virus (HCV), Epstein–Barr virus (EBV), , human T-cell leukemia virus type 1 (HTLV-1), , and high-risk human papillomavirus (HR-HPV) …”
Section: Pin1 and Human Diseasesmentioning
confidence: 99%